Improving Implementation of NCD Care in Low- and Middle-Income Countries: The Case of Fixed Dose Combinations for Hypertension in Kenya - Adrianna Murphy; Daniel Mbuthia; Ruth Willis; Benjamin Tsofa; Mary Gichagua; Peter Mugo; Kara Hanson; Michael R. Reich (Health Systems & Reform)
Health systems in low- and middle-income countries face the challenge of addressing the growing burden of non-communicable diseases (NCDs) with scarce resources to do so. There are cost-effective interventions that can improve management of the most common NCDs, but many remain poorly implemented. One example is fixed dose combinations (FDCs) of medications for hypertension. Included in WHO’s Essential Medicines List, FDCs combine two or more blood pressure lowering agents into one pill and can reduce burden on patients and the health system. However, implementation of FDCs globally is poor. We aimed to identify health systems factors affecting implementation of evidence-based interventions for NCDs, and opportunities to address these, using the case study of FDCs in Kenya. We conducted semi-structured interviews with 39 policy-makers and healthcare workers involved in hypertension treatment policy and identified through snowball sampling. Interview data were analyzed thematically, using the Access Framework to categorize themes. Our interviews identified factors operating at the global, national, county, and provider levels. These include lack of global implementation guidance, context specific cost-effectiveness data, or prioritization by procurement agencies and clinical guidelines; perceived high cost; poor data for demand forecasting; insufficient budget for procurement of NCD medications; absence of prescriber training and awareness of clinical guidelines; and habitual prescribing behavior and understaffing limiting capacity for change. We propose specific strategies to address these. The findings of this work can inform efforts to improve implementation of other evidence-based interventions for NCDs in low-income settings.